Serum sclerostın levels ın chronıc otıtıs medıa wıth and wıthout cholesteatoma - Karali,Elif (2020)
SUMMARY OBJECTIVE Sclerostin is a glycoprotein that plays a catabolic role in bone and is involved in the regulation of bone metabolism by increasing the osteoclastic bone resorption. In this study, serum sclerostin levels were measured in chronic otitis media (COM) with and without cholesteatoma, assuming that it might have a role in the aetiopathogenesis of bone resorption. METHODS A total of 44 patients with cholesteatomatous COM (cCOM) (n = 22) and non-cholesteatomatous COM (ncCOM) (n = 22) were included in this study, and 26 healthy volunteers without any chronic ear disease problem(s) constituted the control group (n = 26). RESULTS No significant difference was not found in terms of serum iPTH, ALP, and vitamin D levels between ncCOM, cCOM, and the control groups. A significant difference was found in terms of serum sclerostin, Ca, and P levels between ncCOM, cCOM, and the control groups (p<0.05). Serum sclerostin levels in the study groups were significantly higher but their serum Ca and P levels were significantly lower compared to the control group. CONCLUSION We think that serum sclerostin concentrations, which were significantly higher in patients with cCOM and ncCOM compared to healthy controls are associated with bone erosion. There is a need for further studies with larger samples in order to determine the relationship between sclerostin and bone erosion in cholesteatoma to help in establishing preventive measures against cholesteatoma and set new targets for the development of non-surgical treatments.